A Novel and Efficient Colorimetric Assay for Quantitative Determination of Amlodipine in Environmental, Biological and Pharmaceutical Samples. Issue 34 (11th September 2019) - Yaqoob, Sana; Rahim, Sana; Bhayo, Adnan Murad; Shah, Muhammad Raza; Hameed, Abdul; Malik, Muhammad Imran
Abstract: Development of facile, on‐spot, robust, and efficient optical nanosensors for drugs and pesticides is one of the active research area. In this study, a nanosensor based on fairly stable silver nanoparticles (AgNPs) conjugated with specially designed thiourea (TU)‐based molecule, N ‐((4'‐methoxy‐2'‐nitrophenyl) carbamothioyl) dodecanamide (TU3 ), was prepared using one pot protocol and characterized by Ultraviolet (UV)‐Visible spectroscopy, dynamic light scattering (DLS), fourier transform infrared (FTIR) spectroscopy and atomic force microscopy (AFM). TheTU3 conjugated AgNPs (TU3‐AgNPs ) were found to be selective spectrophotometric sensor for an antimicrobial drug, amlodipine (Ad), among the pool of different drugs.TU3‐AgNPs based nanosensor allows for the rapid quantitative assay having a detection limit of 0.3 μM in an analytical range of 0.1‐100 μM. The proposed sensor is specific in presence of number of other interfering drugs and other matrix. Upto the best of our literature survey, this is first ever colorimetric sensor for quantification of amlodipine in complex matrix. The specificity of the sensor allows for quantitative detection of amlodipine in environmental, biological and pharmaceutical samples. Abstract : Colorimetric sensors have unique role in drug or toxic environment metabolites sensing. Thiourea based ligand (TU3), N ‐((4′‐methoxy‐2′‐nitrophenyl) carbamothioyl) dodecanamide, conjugated with AgNPs (TU3‐AgNPs) is explored as spectrophotometric sensor that found to be selective for an antimicrobial drug amlodipine (Ad). The role of TU3‐AgNPs as selective sensor allow the detection of amlodipine in environmental, biological and pharmaceutical samples.